The Please Strategy Effect to Improve Paragraph Writing Skill At Universitas of Ibrahimy - Annisa Kurnia Asri (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
Writing skill in English is a productive skill that involves several components such as topic, ideas, main ideas, supporting ideas, sentence structure, grammar, diction, and writing technique. University students must be able to compose well-structured and elaborated academic writing. They are urged to create credible writings in the academic field and one of the strategies that can be used is the PLEASE strategy. PLEASE strategy is a writing strategy that has six steps namely: Pick, List, Evaluate, Activate, Supply, End. Therefore, this research aims to find the effect of the PLEASE strategy to improve English writing skills of the university of students in semester 4 at the English Department, Faculty of Social Science and Humanities University of Ibrahimy Situbondo. The findings of this research were drawn by using Z-test. It shows that the PLEASE strategy can significantly improve students’ writing skills. PLEASE strategy can help students to think systematically and critically using all those 6 steps.